PENINGKATAN HASIL BELAJAR MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA PELAJARAN BAHASA INDONESIA KELAS III B SDN PANDEANLAMPER 03 SEMARANG - Tri Indah Hariyani; Mudzanatun; Aryo Andri Nugroho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background of this research is the condition of class III B students at SDN Pandeanlamper 03 Semarang, who are known to have poor learning outcomes for Indonesian subjects due to the low daily test scores in semester II of the 2022/2023 academic year. The average score is below KKM 70. The aim of the research is to find out the increase in student learning outcomes by using the Problem Based Learning learning model. The learning model used in this Classroom Action Research (CAR) is Problem Based Learning which is carried out during the second cycle. The research subjects were class III B students at SDN Pandeanlamper 03 Semarang with a total of 29 students. The application of the Problem Based Learning learning model can improve student learning outcomes in Indonesian subjects. In the pre-cycle students achieved better learning outcomes of 17.24%. While in Cycle I, learning outcomes increased to 34.48%. And in cycle II managed to experience an increase in learning outcomes of 75.86%. In the context of this statement, it can be seen that the Problem Based Learning learning model can improve and improve student learning outcomes from pre-cycle to cycle II.